2020
DOI: 10.3102/0013189x20943199
|View full text |Cite
|
Sign up to set email alerts
|

African American Parents’ Educational Involvement in Urban Schools: Contextualized Strategies for Student Success in Adolescence

Abstract: Research on parental educational involvement has been organized into three overarching domains—home-based involvement, school-based involvement, and academic socialization. Conventional empirical work in these domains typically centers involvement strategies around White, middle-class experiences rather than examining how optimal parenting approaches vary by race and context. Even fewer studies have explored the manifestations of involvement across these categories in underresourced urban educational settings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…There is a robust body of research that positions parental ethnic-racial socialization as beneficial for Black youth. The current study expands this work by considering concurrently communicated dimensions of ethnic-racial socialization at the intersections of gender and academic socialization (Cooper and Smalls, 2010;Stokes et al, 2020;Cunningham, 2021;Huguley et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
“…There is a robust body of research that positions parental ethnic-racial socialization as beneficial for Black youth. The current study expands this work by considering concurrently communicated dimensions of ethnic-racial socialization at the intersections of gender and academic socialization (Cooper and Smalls, 2010;Stokes et al, 2020;Cunningham, 2021;Huguley et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
“…All this means that the capacity for agency can be slowed down but also activated. To appreciate in detail the characteristics of these effects, we have organized them, inspired by Huguley et al (2021) , in Table 3 , which shows each of the effects reported by the students.…”
Section: Methodsmentioning
confidence: 99%
“…Our analyses accounted for the following potential confounding variables: adolescents’ age, gender, enrollment in a free lunch program (as a proxy for SES, per the American Psychological Association, 2006), baseline perceived ethnic‐racial discrimination from peers and teachers (Fisher, Wallace, & Fenton, 2000), baseline perceived parental cultural socialization (Huguley, Delale‐O’Connor, & Wang, 2020), and the ethnic‐racial diversity of each school's student population (Simpson, 1949).…”
Section: Methodsmentioning
confidence: 99%